2020
DOI: 10.1289/ehp7086
|View full text |Cite
|
Sign up to set email alerts
|

Heatwaves and PM2.5: Sometimes-Surprising Associations with Preterm Birth

Abstract: Extreme heat is linked to higher mortality from a variety of causes ranging from heart disease to heat stroke. 1,2 Climate change is not only raising the global temperatures-with local areas experiencing extreme heatwaves-it may also cause a deterioration in air quality by altering the behavior of primary pollutants and the formation of secondary pollutants. 3,4 A retrospective cohort study published in Environmental Health Perspectives looked at the relationship between fine particulate matter (PM 2:5) combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, a number of studies showed that exposure to air pollution (PM2.5), ozone, and heat was associated with increased risk of preterm birth 9 . Heat and air pollution are independent risk factors of preterm birth 10,11 . Many chemical contaminants, such as nitrate, diisobutyl phthalate metabolites, bisphenol-S, and ethyl paraben have been found to be risk factors for sPTL, 12–14 while 2, 5-dichlorophenol is inversely correlated with overall PTL 14 …”
Section: External Risk Factors Affecting Preterm Labormentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of studies showed that exposure to air pollution (PM2.5), ozone, and heat was associated with increased risk of preterm birth 9 . Heat and air pollution are independent risk factors of preterm birth 10,11 . Many chemical contaminants, such as nitrate, diisobutyl phthalate metabolites, bisphenol-S, and ethyl paraben have been found to be risk factors for sPTL, 12–14 while 2, 5-dichlorophenol is inversely correlated with overall PTL 14 …”
Section: External Risk Factors Affecting Preterm Labormentioning
confidence: 99%
“…9 Heat and air pollution are independent risk factors of preterm birth. 10,11 Many chemical contaminants, such as nitrate, diisobutyl phthalate metabolites, bisphenol-S, and ethyl paraben have been found to be risk factors for sPTL, [12][13][14] while 2, 5-dichlorophenol is inversely correlated with overall PTL. 14…”
Section: Introductionmentioning
confidence: 99%